HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PELAYANAN KEPERAWATAN DI RUANG INAYAH RUMAH SAKIT PKU MUHAMMDIYAH GOMBONG - Khotimah, Nurul; -, marsito; iswati, ning (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
The implementation of therapeutic communication can improvesatisfaction of nursing services in felt by the patient. Therapeuticcommunication that is able to determine patient satisfaction to nursingservice. Lack of communication between the patient interacting with thenurses will nurture good relationships with the families of patients.Patient satisfaction is one indicator in assessing the quality of serviceprovided by a hospital.This research is to determine the relationship between therapeuticnursing communication techniques nursing service satisfaction in a PKUMuhammadiyah Hospital Inayah Gombong. The study was descriptivecorrelative cross sectional design. The analysis technique used is thebivariate analysis with Kendall's tau correlation test at 95% significancelevel.Most patients who were treated at PKU Muhammadiyah HospitalRoom Inayah Gombong states that nurses perform therapeuticcommunication with both (69.8%) and expressed satisfaction of nursingservices in both categories (51.0%).Statistically, there is a relationship between the variables oftherapeutic communication techniques with the satisfaction of nursingservice in PKU Muhammadiyah Hospital Room Inayah Gombong (Ï„ =0.541, pv = 0.000 at Î± = 0.05).Keywords: Therapeutic Communication, Satisfaction, Nursing Services